Review: Winged bean (Psophocarpus tetragonolobus) cropping systems - Graham Eagleton (Society for Indonesian Biodiversity, 2020)
Abstract. Eagleton GE. 2020. Review: Winged bean (Psophocarpus tetragonolobus) cropping systems. Biodiversitas 21: 5927-5946. Winged bean (Psophocarpus tetragonolobus (L.) DC.) is a rambling, nitrogen-rich, leguminous crop of the Old-World tropics. This review of winged bean (WB) within cropping systems of Southeast Asia and Melanesia revisited four traditional roles that the crop has played: as a minor courtyard vegetable of villages and suburbs throughout the region; as a popular tuber crop in the irrigated plains of Tada-U township in Central Myanmar; as a companion crop in the mixed garden fields of Wamena in Indonesian New Guinea; and as a niche tuber crop in rotation with sweet potato near Goroka in Papua New Guinea (PNG). Drawing upon such traditions, researchers since the 1970s have identified potential new roles for winged bean. In Malaysia, vegetable pod yields up to 35 t ha-1 over a 25-week growing period have been obtained from solidly trellised, branching cultivars. Ratooning the crop through a further two cycles covers the cost of the trellising. Tubers from un-trellised field crops in Myanmar, and of staked, pruned garden crops in highland PNG have been estimated to produce crude protein yields of at least 300 kg ha-1 and 600 kg ha-1, respectively. Synergies between the gene-pools and cultural traditions would be expected to expand the range, raise the yield and stabilize the quality of tuber crop production. Researchers in Sri Lanka intercropped maize with winged bean. At optimal plant densities, they recorded a corn cob yield of 5 t ha-1 together with a cumulative winged bean fresh pod yield of 27 t ha-1. In Kentucky (380N), the combination of maize with winged bean to produce silage resulted in 11-18% greater biomass with 39-67% greater nitrogen per hectare than maize monocrop control plots. Branching winged bean cultivars have significant potential for benign, high-nitrogen cover and forage crops. Promiscuous nodulation and the development of storage root-systems compensate for slow initial top growth which then accelerates to produce a substantial yield of highly digestible leaf protein and vitamins. Hard-seededness and daylength-sensitive phenology are significant, surmountable, barriers to an expanded role for winged beans.